2014
DOI: 10.4103/0976-9668.127280
|View full text |Cite
|
Sign up to set email alerts
|

Study of extended spectrum β-lactamase producing Enterobacteriaceae and antibiotic coresistance in a tertiary care teaching hospital

Abstract: Aims:To study the prevalence of extended spectrum β-lactamase (ESBL) producing Enterobacteriaceae and coresistance to other commonly used antibiotics from the Bhopal region of Central India.Settings and Design:A prospective study was conducted from September 2011 to August 2012 in Microbiology Department of our tertiary health care center.Materials and Methods:A total of 1044 Enterobacteriaceae isolates were recovered from various specimens. ESBL production was detected by using Clinical Laboratory Standard In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
30
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 24 publications
31
30
5
Order By: Relevance
“…This could be attributed to the association of multi drug resistance in ESBL producing isolates as they carry co-resistance genes for other non -β-lactam antibiotics and thus limiting the therapeutic options [10]. The ESBL detection in our study was 47.4% which was in concordance with other studies [11][12][13]. ESBL production was highest in E.coli isolates (53.08%) followed by K.pneumoniae 27 (50%) which was similar to studies done by Shiju, et al, and Linda, et al [9,14] 33.33% of the Pseudomonas spp.…”
Section: Fig-1 Phenotypic Confirmatory Disc Diffusion Test Discussionsupporting
confidence: 82%
“…This could be attributed to the association of multi drug resistance in ESBL producing isolates as they carry co-resistance genes for other non -β-lactam antibiotics and thus limiting the therapeutic options [10]. The ESBL detection in our study was 47.4% which was in concordance with other studies [11][12][13]. ESBL production was highest in E.coli isolates (53.08%) followed by K.pneumoniae 27 (50%) which was similar to studies done by Shiju, et al, and Linda, et al [9,14] 33.33% of the Pseudomonas spp.…”
Section: Fig-1 Phenotypic Confirmatory Disc Diffusion Test Discussionsupporting
confidence: 82%
“…Similar pattern of Klebsiella spp. ESBL producer also noticed accounting to 45.0%, which is somewhat similar to that found in the study from parts of India and Iran [11, 29], but were comparatively lesser than reported from Rajasthan, 67.0% [30]. Our finding of higher ESBL producers among E.coli , is in conformity with some of the previous studies [11,13].…”
Section: Discussionsupporting
confidence: 91%
“…Klebsiella spp. and E. coli were reported as the most common Enterobacteriaceae isolates, similar to earlier findings [11, 12, 13]. However, the distribution is not in concordance to those observed earlier, in our case Klebsiella spp.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Endemic transmission of ESBL-producers can be controlled by appropriate infection control measures and prudent antibiotic management interventions [4]. Reliable detection of ESBL-producers by clinical microbiology laboratory is essential to provide appropriate therapy and to control nosocomial outbreaks [9,10].…”
Section: Introductionmentioning
confidence: 99%